2018
DOI: 10.1016/j.clnu.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Association of general and central obesity with hypertension

Abstract: By using International WHO and standard Indonesia classification systems, general and central obesity were associated with hypertension in Indonesia women. Thus, not only general obesity but also central obesity should be used to assess obesity in Indonesian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 20 publications
5
64
0
3
Order By: Relevance
“…In a cohort of 17,803 pregnant Chinese women, the copresence of a higher BMI and WC interacts to further increase the risk of gestational diabetes mellitus [35]. In addition, RISKESDAS research showed that only when general obesity or overweight coexisted with central obesity was the prevalence of hypertension signi cantly increased [13]. This nding supported the stable relation between excess body fat and blood pressure.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In a cohort of 17,803 pregnant Chinese women, the copresence of a higher BMI and WC interacts to further increase the risk of gestational diabetes mellitus [35]. In addition, RISKESDAS research showed that only when general obesity or overweight coexisted with central obesity was the prevalence of hypertension signi cantly increased [13]. This nding supported the stable relation between excess body fat and blood pressure.…”
Section: Discussionmentioning
confidence: 78%
“…Accumulating evidence suggests a potential link between obesity-related hypertension [12][13][14], but controversy exists about the degree of the associations between two anthropometric indicators and the risk of hypertension. Nonetheless, information about the relationship between BMI, WC and hypertension is limited in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, overweight and obesity are probably favorable to the possibility of being hypertensive (Francischetti and Genelhu, 2007). Many previous studies show that overweight and obesity are strongly and considerably correlated to increases in the risk of high blood pressure in many developing countries, for examples Nurdiantami et al (2017) for Indonesia, and Cao et al (2017) for China. This study confirms the findings from the literature by providing a causal inference that overweight or obesity causally increases the probability of hypertension for both men and women compared to under or normal weight.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, body mass index a common measure of body weight is strongly and positively correlated with the risk of hypertension in many countries such as Argentina (Stray-Pedersen et al, 2009), Norway (Stray-Pedersen et al, 2009), the United States (Kumanyika, 1989;Shihab et al, 2012), China (Li et al, 2017), Iran (Poorolajal et al, 2016), Japan (Lee et al, 2004;Jiang et al, 2003;Nurdiantami et al, 2017), Indonesia (Tuan et al, 2009) and Vietnam (Tuan et al, 2009). For example, Li et al (2017) find that compared to an individual with normal weight, individuals with overweight and obesity are more likely to be hypertensive by roughly double and triple than a normal individual in China.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos epidemiológicos demonstram por sua vez que a obesidade central está altamente associada à hipertensão (Gao et al, 2016;Nurdiantami et al, 2018), à presença de diabetes tipo 2 (Caspard et al, 2018), à doença coronariana (Fuster et al, 2016) e ao aumento da mortalidade cardiovascular (Lee et al, 2018 Apesar do IMC ser simples, prático, sem custo, Garn et al, já apresentava algumas limitações quanto ao uso desta avaliação antropométrica, podendo haver diferenças na composição corporal em função do sexo, idade, etnia, prática de atividade física ou sedentarismo, na presença de perda de estatura em idosos devido a cifose, ou em indivíduos edemaciados o que, segundo os autores, colocariam em risco a utilização do IMC como indicador de gordura corporal (Garn et al, 1986). Estudos mais recentes continuam a manter cuidados na interpretação desta medida antropométrica, a qual não reflete a distribuição da gordura corporal, e indivíduos com o mesmo IMC podem apresentar níveis diferentes de massa gordurosa visceral (Neeland et al, 2018;Piche et al, 2018).…”
Section: Obesidade E Risco Cardiovascularunclassified